Dye-Sensitized Solar Cells Based on Carbon Nanoparticle Counter Electrode - Muliani, Lia; Nursam, Natalita (LIPI Press, 2012)
The performance of dye-sensitized solar cells (DSSC) is affected by its components. One of the affecting factors is counter electrode. Counter electrode has a function as a catalyst to fasten reaction kinetics during the tri-iodide reduction reaction within the cell. In this paper, the fabrication process of DSSC based on carbon nanoparticle counter electrode is described. The carbon nanoparticle was prepared into carbon paste with variation of solvent. The carbon nanoparticle paste was deposited onto FTO glass substrate (fl uorine-doped tin-oxide) by screen printing tehnique using stainless steel screen. The Characteristic of I-V curve of carbon counter electrode cells was measured using Oriel Sun simulator AM 1.5 with the light intensity of 40 mW.cm-2. The result was compared to cells which are based on platinum counter electrode. The best effi ciency of the cell obtained was 2.0%. and 3,12% for carbon nanoparticle and platinum counter electrode, respectively.